The Messinian (Late Miocene) coral reefs in the Cabo de Gata-Níjar UNESCO Global Geopark - Juan Braga; Jose Martin; Gloria Garcia-Hoyo; Lucia Tejero-Trueque (Geoconservation Research)
Neogene sedimentary rocks cover extensive areas of the Cabo de Gata-Níjar UNESCO Global Geopark (Almería, SE Spain) although most of the outcropping rocks are Miocene volcanics. The post-volcanic sedimentary rocks include three successive Messinian coral reef units. The lower reefs consist of coral patches of varying dimensions comprising Porites and Tarbellastraea, which grew on carbonate ramps. The second unit is Porites fringing reefs that prograded from shorelines. These two lower units, early Messinian in age, were subaerially exposed and eroded during a relative sea-level drawdown, probably coeval with the Mediterranean Messinian salinity crisis. The last, late Messinian reef unit onlaps the erosion surface and consist of small Porites patches that grew dispersed in oolitic shoals together with microbial carbonates. These low-diversity reefs are the last zooxanthellate coral reefs in the Mediterranean basin and constitute the endpoint of decreasing coral diversity in the region during the Miocene due to disconnection from the Indian Ocean and global cooling. The good exposures and accessibility of these reefs in the arid landscape of the Geopark make them valuable sites for practical training in geology and paleontology at different levels and reference sites for geotourism.